CONSTRAINTS PERCEIVED BY GOAT FARMERS IN CERTAIN ADOPTED VILLAGES OF ASSAM - B. N. SAIKIA7, R. GOSWAMI1; D. C MILI2; N. NAHARDEKA3 A. K. GOGOI4; M. C. BORA5; R. ROYCHOUDHU (Indian Journal of Animal Production and Management, 2017)
A study on the constraints faced by adopted and non-adopted goat farmers in threerural villages of Assam viz. Nahira, Tepesia and Tetelia adopted by â€œAll India Co-ordinatedResearch Project on Goat Improvementâ€, Goat Research Station, Assam AgriculturalUniversity, Byrnihut, Guwahati indicated that the major constraints perceived by the adoptedand non-adopted goat farmers were inadequate grazing facility (38.10 and 28.57%), highcost of feeds (29.52 and 31.43%), lack of knowledge about scientific management of goats(0 and 39.05%), inadequate availability of breeding buck (0 and 30.48%), inadequateveterinary services (0 and 27.62%), lack of financial facility (45.71 and 65.71%), poor creditfacility (29.52 and 31.43%), exploitation by middleman (40.95 and 52.38%) and predatorsattack (29.52 and 30.48%) respectively.